2018
DOI: 10.1186/s12864-018-4651-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional development of phospholipid and lipoprotein metabolism in different intestinal regions of Atlantic salmon (Salmo salar) fry

Abstract: BackgroundIt has been suggested that the high phospholipid (PL) requirement in Atlantic salmon (Salmo salar) fry is due to insufficient intestinal de-novo synthesis causing low lipoprotein (LP) production and reduced transport capacity of dietary lipids. However, in-depth ontogenetic analysis of intestinal PL and LP synthesis with the development of salmon has yet to be performed. Therefore, in this paper we used RNA-Seq technology to investigate the expression of genes involved in PL synthesis and LP formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 25 publications
0
23
2
Order By: Relevance
“…The method for handling RNA‐seq data has been described in detail in previous studies (Gillard et al., 2018; Jin et al., 2018). In brief, read sequences were quality trimmed using cutadapt (version 1.8.1) before being aligned to the salmon genome ( icsasg _version 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method for handling RNA‐seq data has been described in detail in previous studies (Gillard et al., 2018; Jin et al., 2018). In brief, read sequences were quality trimmed using cutadapt (version 1.8.1) before being aligned to the salmon genome ( icsasg _version 2).…”
Section: Methodsmentioning
confidence: 99%
“…To visualize expression levels between different genes and tissues, normalized counts in the form of transcripts per million (TPM) values were generated. Raw gene counts were first divided by their mRNA length in kilobases to normalize for transcript length, and then divided by the total number of counts from each library to normalize for sequencing depth (Jin et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…We approach this question by 93 running a feeding trial with both domesticated and wild salmon that are fed contrasting diets 94 rich in either FO, VO or PL and then perform comparative transcriptomic and fatty acid 95 analyses of two tissues involved in lipid uptake (pyloric caeca) and endogenous synthesis of 96 LC-PUFAs (liver). Our study shows clear differences between metabolism in the wild and 97 domestic salmon genetic backgrounds and suggests that the regulation of genes involved in 98 The method for handling RNA-sequencing (RNA-seq) data has been described in detail in 165 previous studies (Gillard et al, 2018;Jin et al, 2018). In brief, read sequences were quality 166 trimmed using Cutadapt (v1.8.1) before being aligned to the salmon genome (ICSASG_v2).…”
mentioning
confidence: 99%
“…In line with this idea, our study found that apoa1_2 gene was strikingly higher 441 expressed in liver in domesticated compared to wild salmon, regardless of dietary lipid 442 composition ( Figure 5). Although the existence of lipoproteins and their apolipoprotein 443 composition is not well described in fish, it is suggested that they should be similar to mammals 444 (Jin et al, 2018). The higher expression levels of apoa1_2 transcripts could therefore be one 445 factor that contributes to fast growth of domesticated salmon, as this gene is key to the 446 lipoprotein assembly and thereby transport of lipids between liver and other tissues such as 447 muscle and adipose tissue (Xu et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation